Estudo de nanoestruturas híbridas como sistemas avançados para o transporte e liberação de 5-fluorouracil na terapia contra o câncer - TEIXEIRA, Elaine Nunes da Silva (2022)
5-Fluorouracil (5-FU) is a chemotherapeutic agent widely used for the treatment of several types of solid tumors. However, due to its low specificity, it presents high toxicity on the gastrointestinal tract and non-selective action against healthy cells. In this sense, the objective of this work was to prepare and characterize a hybrid material based on carbon quantum dots (CQD) which are combined with the intercalation compound composed by 5-FU drug and the Layered Double Hydroxide (LDH) inorganic solid, in order to develop a system that presents capacity of transport and release of the chemotherapeutic agent to specific target cells. The resulting system (CQD@LDH-5FU) and its isolated compounds were characterized using different physicochemical and analytical techniques. From spectroscopy techniques and optic properties analysis it was possible to identify the presence of CQD in the hybrid. The FTIR spectra suggested that the main interactions between the CQD with the drug and LDH lamellae is established by hydrogen bonds. Furthermore, the intercalation of the drug into the hybrid granted it higher thermal stability, as pointed out by DSC studies. SEM images demonstrated that the physical mixing of CQD and LDH-5FU did not cause destruction of the lamellar structure of the LDH. The minimum formulas obtained from EDS confirmed the presence of the elements Mg, Al and O in the hybrid indicating a homogeneous distribution of Mg and Al in the lamellae of the LDH. The release assays showed that the chemotherapeutic agent released by the CQD@LDH-5FU system denotes higher release selectivity in the tumor environment (pH 5.0).